Relationships between broiler final weights and microbiota of certain segments of the intestine. (September 2019) - Baltic, B M; Janjic, J; Brankovic Lazic, I; Mrdovic, B; Ciric, J; Markovic, R; Mitrovic, R
Abstract: Only healthy animals can expect good production results. Gastrointestinal tract (GIT) health is of particular importance in broilers. GIT health has been protected by antibiotics as growth promoters for years. Since their use is forbidden, alternatives are required. One alternative is the use of medium chain fatty acid (MCFA) in broiler nutrition, in order to ensure the health of digestive tract, that is, prevent the activity of pathogenic bacteria, coccidias and viruses. Today, commercial MCFA supplement is used on the market in nutrition of broilers and piglets. Previous experiences of using MCFA in nutrition of broilers suggest that MCFA can be used as a substitute for antibiotics. In the duodenum of experimental broilers (a group of birds fed with added MCFA), the numbers of Enterococcus spp. and E. coli were significantly correlated with bird weight, but this was not the case in other intestinal segments (ileum or caecum).